Citation analysis of the characteristics of the history academics in Singapore. - Lee, Wei Wei. (2008)
This study presents an analysis of 1506 citations drawn from a sample of 12 articles published by History lecturers from the History Department of the National University of Singapore. The objective is to find the characteristics of the materials used by historians. The results suggest a high usage of non-serial form of publications with significant concentration on the use of archival materials especially manuscripts in public records offices overseas. Citations to books were at 19.39% and citations to journals and periodicals were 11.49%. Materials published in United Kingdom were the most frequently used.The results when compared to other similar studies showed that history academics in singapore demonstrate similar characteristic with their counterparts in the United States.